Three-dimensional analysis of braced excavation in clay - Tan, Thai Wu (2017)
Plane-strain (2D) finite element analysis is commonly carried out in the design of braced excavation system due to its simplicity in modeling. Since the effect of excavation length is usually not accounted for in plane-strain analysis, when the braced excavation is short, the effect is significant and cannot be modeled in 2D way. In this case, three-dimensional analysis is recommended. This project has dual aims. Firstly, three-dimensional (3D) finite analyses are conducted to investigate the influences of design parameters including excavation length, wall stiffness and soil strength on the performance of the retaining wall system. The excavation responses are examined in terms of lateral wall deflections, compressive strut forces and basal heave stability of the excavation system. Secondly, this project attempts to establish the correlation between 2D and 3D analyses. A total of 6 plane-strain finite element simulations and 30 three-dimensional finite element simulations were modeled using PLAXIS 2D and PLAXIS 3D Foundation software, respectively. The results obtained from both types of analyses are compared in terms of Plane Strain Ratio (PSR). PSR is defined as the ratio of maximum lateral wall displacement in three-dimensional analyses to plane-strain analyses. As compared to three-dimensional analyses, plane-strain analyses always yield a more conservative result. When the excavation length to depth ratio is greater than 6 and length to width ratio is greater than 5, the maximum lateral wall movements computed from both 2D and 3D analyses are similar. For the cases considered, the results show that the retaining wall with higher stiffness tends to yield smaller lateral wall displacements and exert larger compressive forces on the horizontal struts. The soil with higher undrained shear strength results in smaller lateral wall displacements and compressive strut forces. The results also show that the effect of system stiffness and undrained shear strength of soil on basal heave stability are negligible.